A Study of Tourism Destinations Planning and Spatial Analysis in Ciletuh-Palabuhan Ratu Geopark - Indra Wardana, Andreas; Firmansyah, Ade; Dian Mawarni, Ida Ayu Sawitri (Journal of Indonesian Tourism and Development Studies, 2026)
Tourism planning plays a crucial role in ensuring inclusive and sustainable development by balancing economic growth with environmental conservation. This study aims to examines the tourism planning framework in Ciletuh-Palabuhan Ratu Geopark, focusing on key tourism elements: attractions, amenities, accessibility, and the spatial context of Ciemas Sub-district. This geopark has the potential to support the local economy through its unique geological features and cultural heritage. However, this potential has yet to provide optimal socio-economic benefits to local communities. A qualitative descriptive approach was applied, integrating literature review, stakeholder interviews, field-based observations. Spatial analysis was conducted using GIS through overlay techniques incorporating topography, contour intervals, road networks, rivers, settlement patterns, tourist attractions, and protected areas. The results identified nine major tourist attractions categorized into marine, landscape, and geotourism, with the Ciletuh Mega Amphitheater serving as the spatial landmark. While local amenities reflect sustainable architectural characteristics, accommodation capacity remains limited. Accessibility is limited by the lack of public transport and poor road conditions in several strategic areas. The study delineates tourism planning zones covering 4,827.35 ha and proposes an integrated tourism trail connecting major attractions. These findings provide a strategic basis for environmentally sustainable tourism development aligned with geopark’s conservation objectives.